Fine mapping of the human SCIDX1 locus at Xq12-13.1. - Markiewicz, S; DiSanto, J; Chelly, J; Fairweather, N; Le Marec, B; Griscelli, C; Graeber, M; Müller, U; Fischer, A; Monaco, A (1993)
Previous linkage analysis of families with X-linked severe combined immunodeficiency (SCIDX1) mapped this locus to a large region encompassing about 10 to 20 cM at Xq12-21. We have analyzed in SCIDX1 families the segregation of 7 highly polymorphic microsatellites repeats localized to this region, including a new polymorphic microsatellite at the DXS135 locus described in this study, to refine the mapping of this disease locus. The observations of genetic recombinants within the previously defined SCIDX1-region allow us to establish new flanking markers at the DXS135 and DXS227 loci, which significantly reduce the region harboring the SCIDX1 locus to a distance estimated between 3 to 5 cM. The existence of multiple, highly polymorphic markers in the refined SCIDX1 region will greatly improve the accuracy of carrier detection and prenatal diagnosis for SCIDX1.